A nova fronteira do Capital: a financeirização e o processo de gentrificação na região da Luz em São Paulo - Pimenta, Ana Clara de Almeida (2020)
The intersection between financial capital and the state is an analytical key for understanding the form taken by urban public policies in recent decades. The fiscal crisis, associated with the centrality of finance and a new model of urban planning, brought a “new formula” composed of the articulation between public and private agents with the objective of making urban operations possible. Within this equation, revitalization policies are born out of the dialectical tension between collective insurgency movements that fight for the realization of the right to the city and the appropriation of these projects by financial capital. In this scenario, this work discusses how the financialization process takes place in a Special Areas of Social Interest and how it interrelates with the phenomenon of gentrification. The study is part of a discussion on the revitalization policy in the region of Luz in São Paulo, carried out through public-private partnerships. The dissertation hypothesis consists in the statement that the Special Areas of Social Interest emerge as new frontiers for capital articulated with the Public Power through public-private partnerships. In this sense, the finite characteristic of the land as a commodity acts as a guiding thread for the new role that the State assumes, which has the function of "unlocking" geographically privileged locations and that for various reasons would not be available to the market. However, at the epicenter of this phenomenon, there is a significant contingent of people who have an identity link with the place and constitute movements of resistance to the force of expulsion exerted by the process of financialization of space.